Comfortable urban environment as a basis for social adaptation of people with disabilities - V. I. Khabarov; S. V. Bruev (Путеводитель предпринимателя)
An urban environment with comfort zones is an important condition of modern human life, in particular, it is directly related to people who have limited mobility. The lack of necessary infrastructure makes it impossible for people with disabilities to solve everyday problems and issues.The term «accessible» or «barrier–free» environment is mentioned in many legislative acts, and has different interpretations in different sources. It should be noted that the importance of this problem has been gaining momentum in recent years, the problem of the quality and accessibility of the urban environment for people with disabilities in everyday life is beginning to come to the fore.State authorities are creating the necessary conditions for people with disabilities, which are aimed at developing services, helping to overcome barriers that prevent people with disabilities from taking full part in society. People are rethinking the quality problem anew and accessibility of the urban environment for the disabled, develop special programs to improve the quality of the urban environment.This article will help to analyze the main components of a comfortable urban environment for people with disabilities, there is a set of measures, problems, solutions that help to form a comfortable urban environment for various categories of the population.